Preliminary analysis of dimming property for visible light communication - Ahmad Zabidi, Suriza; Akter, Sharmin; Zainal Abidin, Mohd. Shahnan (IEEE, 2018)
Visible light communication (VLC) is an emerging and promising new technology in optical wireless communication (OWC). However, dimming affects the performance of the visible light communication system. In visible light communication (VLC) system, illumination and communication both are provided simultaneously using light-emitting diode (LED). The dimming control applicable and required for the lighting system. There are different modulation techniques for dimming control in visible light communication. In this paper, only the NRZ-OOK modulation method is investigated for different dimming range, transmission distance, beam divergence angle and bit rate. Optisystem Software is a tool that analyze the performance of the system. The result shows that by increasing the link from 10 m to 63 m, the obtained BER is 6.16656×10-9, Q factor is 5.6919 and 400kb/s data speed. However, the achieved data rate is still unsatisfactory for the VLC system. We increased the data rate from 400kb/s to 2Mb/s, but the distance between transmitter and receiver decreased to 3m by maintaining BER of 1.33827×10-9. It means that high-speed data transmission by using NRZ-OOK is for short distance only. The scope of this research excluded the following parameters which are shadowing, mobility, multipath interference and intersymbol interference for multicarrier modulation. These are the related research topic which is for future work.